2012
DOI: 10.3340/jkns.2012.52.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Significance of Ligamentum Flavum Hypertrophy in the Occurrence of Redundant Nerve Roots of Central Lumbar Spinal Stenosis

Abstract: ObjectiveThere were previous reports of redundant nerve roots (RNRs) focused on their clinical significance and pathogenesis. In this study, we investigated the significant radiologic findings that correlate with RNRs occurrence. These relations would provide an advanced clue for clinical significance and pathogenesis of RNRs.MethodsRetrospective research was performed with data from 126 patients who underwent surgery for central lumbar spinal stenosis (LSS). Finally, 106 patients with common denominators (int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
7
26
0
Order By: Relevance
“…1). In the remaining 40% of patients, redundant nerve roots (RNRs) of the cauda equina are evident on preoperative magnetic resonance images (MRIs) [2][3][4][5]. RNRs were first described by Verbiest [6] in 1954, and they were named 14 years later by Cressman and Pawl [7].…”
Section: Introductionmentioning
confidence: 99%
“…1). In the remaining 40% of patients, redundant nerve roots (RNRs) of the cauda equina are evident on preoperative magnetic resonance images (MRIs) [2][3][4][5]. RNRs were first described by Verbiest [6] in 1954, and they were named 14 years later by Cressman and Pawl [7].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have analyzed cross-sectional areas of intracanal-occupying lesions, such as lumbar disc herniation, burst fracture, ligamentum flavum, and ossification of the posterior longitudinal ligament [3456]. Some authors have reported a correlation of clinical symptoms with both the cross-sectional area of the dural sac and the extent of lumbar canal stenosis [78910111213].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because cauda equina schwannomas may move craniocaudally, we should consider the influence of tumor mobility in the dural sac [41516171819]. Hence, further investigation examining tumor mobility is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a retrospective study of patients who underwent EDX because of neurological symptoms of the lower extremity and lumbosacral MRI for suspected spinal structural lesions between July 2014 and August 2017. The inclusion criteria were (1) an interval of less than 3 months between EDX and MRI; (2) abnormal EDX findings necessarily including abnormal spontaneous activity (positive sharp waves or fibrillation potentials) in lower extremity muscles; and (3) upper lumbar (L1/2, L2/3, or L3/4) central canal stenosis, defined as a CSA of the dural sac of <100 mm 2 on lumbar spine MRI . The exclusion criteria were (1) concomitant peripheral polyneuropathy suspected by clinical manifestations and diagnosed by a nerve conduction study (NCS); (2) structural lesions on MRI at the L4/5 or L5/S1 level in the spinal canal or the neural foramina that could explain the EDX abnormalities; and (3) acute cauda equina syndrome, characterized by a rapid progression of neurological deficits, including bladder and bowel dysfunctions or sensory changes in the perineal area; and (4) a history of lumbar spine surgery whose current symptoms developed before the surgery or within 1 year after surgery.…”
Section: Methodsmentioning
confidence: 99%